Reporting on the Role of miRNAs and Affected Pathways on the Molecular Backbone of Ovarian Insufficiency: A Systematic Review and Critical Analysis Mapping of Future Research - Rapani, Anna; Nikiforaki, Dimitra; Karagkouni, Dimitra; Sfakianoudis, Konstantinos; Tsioulou, Petroula; Grigoriadis, Sokratis; Maziotis, Evangelos; Pantou, Amelia; Voutsina, Aikaterini; Pantou, Agni; Koutsilieris, Michael; Hatzigeorgiou, Artemis; et al. (Frontiers in Cell and Developmental Biology, 2021)
Ovarian insufficiency is identified as a perplexing entity in the long list of pathologies impairing fertility dynamics. The three distinct classifications of ovarian insufficiency are poor ovarian response, premature ovarian insufficiency/failure and advanced maternal age, sharing the common denominator of deteriorated ovarian reserve. Despite efforts to define clear lines among the three, the vast heterogeneity, and overlap of clinical characteristics renders their diagnosis and management challenging. Lack of a consensus has prompted an empirically based management coupled by uncertainty from the clinicians’ perspective. Profiling of patients in the era of precision medicine seems to be the way forward, while the necessity for a novel approach is underlined. Implicating miRNAs in the quest for patient profiling is promising in light of their fundamental role in cellular and gene expression regulation. To this end, the current study sets out to explore and compare the three pathophysiologies -from a molecular point of view- in order to enable profiling of patients and enrich the data required to practice individualized medicine. Following a systematic investigation of literature, data referring to miRNAs were collected for each patient category, and a subsequent KEGG analysis interpreting these miRNAs provided a summary of the affected pathways. A literature review on the most crucial of the detected pathways was performed to reveal their relevance to fertility deterioration. All three pathophysiologies presented sharing common ground regarding the affected pathways, naturally attributed to the common denominator of ovarian insufficiency. Alarming discrepancies among publications were revealed, pertaining to employment of empirical and arbitrary criteria in categorizing the patients. Following bioinformatic analysis, the final step of the current study consisted of a critical analysis of the molecular data sourced, providing a clear and unique insight into the physiological mechanisms involved. It is our intention to contribute to mapping future research dedicated to ovarian insufficiency and to help researchers navigate the overwhelming information published in molecular studies.